Dislocation creep behavior of CoCrFeMnNi high entropy alloy at intermediate temperatures. Issue 12 (2nd December 2018) - Kang, You Bin; Shim, Sang Hoon; Lee, Kap Ho; Hong, Sun Ig
ABSTRACT: Dislocation creep behaviors of CoCrFeMnNi were investigated at intermediate temperatures. Shape of creep curves, stress exponents and the activation energies at high stresses (>40 MPa) were distinctly different from those at low stresses, suggesting the transition of creep mechanism from climb-controlled creep to viscous glide creep. Lattice strain energy of dislocations plays an important role on the distribution of atoms over the configurational entropy in the vicinity of dislocation. The excellent agreement between the experimental transition stress and the theoretical stress using the data of Cr suggests that Cr is the most influential element to the viscous glide at high stresses. GRAPHICAL ABSTRACT: IMPACT STATEMENT: We report climb-to glide-creep transition in CoCrFeMnNi first time. The transition to viscous glide is attributed to dragging of dislocations caused by change of dislocation-line-energy and mobility of segregated atoms.